Effect of the magnesia and alumina in the modified-supported perovskite-type catalysts for the dry reforming of methane. (15th October 2021) - Kumar Yadav, Pradeep; Das, Taraknath; Mondal, Prasenjit
Graphical abstract: Abstract: A series of supported perovskite-type catalysts were synthesized. The support (SiO2 ) was modified with alumina and magnesia to prepare the modified-supported catalysts. The synthesized catalysts were assessed for DRM reaction for the production of syngas. The surface area of the synthesized catalyst increased with addition of ceria in a certain ratio (x = 0.05). The surface area did not change significantly as the support-modified with alumina or magnesia. The nickel-aluminate and nickel-magnesia solid solution were observed in the modified-supported perovskite catalysts. It assisted in improving the surface basicity of silica, and increasing the percent conversion and percent product yield. The optimum ratio of reactant (methane and carbon dioxide) in the feed stream was suggested to be 1. The ratio of H2 /CO increased (>1) as increasing the methane to carbon dioxide ratio suggested that the methane cracking dominated over DRM. The carbon deposition over the catalyst surface was due to the methane cracking reaction. The carbon deposited in all catalysts however; the activity of the catalyst was unaffected. The most effective catalyst was found to be 40LaNi0.75 Ce0.05 Zr0.20 O3 /8MgO-SiO2 .